Activization of cognitive activity of future primary school teachers (Pedagogy of Higher and Secondary Education, 2013)
Talash I. O. Activization of cognitive activity of future primary school teachers.In article attempt to define a way of activization of cognitive activity of students of psychological and pedagogical faculty in the course of introduction of modular and rating technology of training is carried out.
Keywords: cognitive activity; cognitive motives; module; block; modular and rating technology